Práticas clínicas da psicologia frente ao sofrimento psíquico causado pelo desemprego contemporâneo - Cruz, Daniel Viana Abs da (Universidade do Vale do Rio do Sinos, 2008)
This research intends to contribute to understandings of the psychologist’s practices towards psychological suffering caused by unemployment. Upon using qualitative research methods the author tries to broaden our comprehension of Psychology’s activities and interventions in contemporary clinical practices of professionals linked to different theoretical perspectives. This thesis consists of a research report which contains the information about the research, a paper which presents the theoretical refelctions that guided the development of this research and a paper which discusses the data collected. Unemployment is defined in the intersection of Labour Psychology and Clinical Psychology. Hence, the thesis discusses the importance of development of a Labour Clinic which might be able to integrate these tow distinct perspectives. The studeis which deal with the effects of unemployment over mental health are discussed in order to emphasize the importance of development of clinical interventions that deal with u
Keywords: desemprego; saúde mental; psicologia clínica; clinical psychology; mental health; unemployment; Ciências Humanas